Consequences of Spiritual Care for Cancer Patients and Oncology Nurses: a Qualitative Study - Soolmaz Moosavi; Camelia Rohani; Fariba Borhani; Mohammad Esmaeel Akbari (Elsevier, 2019)
Objective: The nature of cancer increases the spiritual needs of patients and necessitates the provision of holistic care for them. By trying to meet the spiritual needs of patients, oncology nurses can help them adapt, gain inner peace, and develop positive thoughts and attitudes. This study aimed to explore the consequences of spiritual care for cancer patients and oncology nurses from the perspective of the patients, family members, nurses, and other health-care team members. Methods: The present qualitative study was conducted using conventional content analysis in 2016-2017. The data were collected through semi-structured deep interviews of the 18 participants. Results: The theme extracted from the data was "spiritual growth" and comprised the major categories of "nurse's spiritual development" and "patient's spiritual development." There were three subcategories in the nurse's spiritual development and 11 subcategories in the patient's spiritual development. Conclusions: Spiritual care places the cancer patient and the oncology nurse on the path to spiritual growth. The achievement of peace by the patient and the nurse was a common consequence of spiritual care. It helps the nurse promote comfort and a sense of peace in the patient and eventually to obtain inner satisfaction. Considering the transcendental effects of spiritual care, a systematic plan should be devised to enhance sensitivity in oncology nurses and encourage them to make spiritual care a component of interventional plans.